Pengaruh Electronic Word of Mouth dan Brand Image terhadap Minat Beli Tandon Air Marine di Kota Surabaya - Dimas Akbar Ramadhan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The use of water reservoirs is increasingly diverse but the aims still to save clean water, making the competition between water reservoir producers in Indonesia more competitive. That is added with the emergence of various brands of new water reservoirs that are produced and circulated throughout Indonesia. Moreover, the types of water reservoirs that appear are also increasingly varied. The number of brands of water reservoirs in Indonesia with various types of marketing affects consumer buying interest in the water reservoir itself. This study aims to determine the effect of Electronic Word of Mouth and Brand Image on Buying Interest. By using associative methodology and in taking the sample using purposive sampling technique. The results of this study note that Electronic Word of Mouth and Brand Image simultaneously and partially affect Purchase Interest. The company should maintain and further improve the supporting factors in order to form a Brand Image that has a positive influence on buying interest from consumers. Keywords: Electronic Word of Mouth, Brand Image, Buying Interest